Isolasi dan Identifikasi Microsporum canis dari Anjing Penderita Dermatofitosis di Yogyakarta (ISOLATION AND IDENTIFICATION OF Microsporum Canis FROM DERMATOPHYTOSIS DOGS IN YOGYAKARTA) - Indarjulianto, Soedarmanto; ., Yanuartono; Purnamaningsih, Hary; Wikansari, Puspa; Sakan, Gerson Yohanes Imanuel (Jurnal Veteriner, 2014)
Dermatophytosis in dogs can be caused by one species of dermatophytes group called Microsporumcanis. This study aims to isolation and identification of M. canis in dogs suspected dermatophytosis inYogyakarta. Skin scrapings from 50 dogs that clinically showed lesions such as combination of alopecia,erythema, papules, pustules, scaly and crusty used in this study. Samples of skin scraping were culturedin the Sabouraud’s dextrose agar media for fungi identification macroscopically and microscopically. Theresults showed that 17 of 50 samples (34%) grown on SDA medium from 2 to 18 days after cultivation. Thecolony grew with flat topography and slightly reflexed, the surface of the colony looks like a thick fur, whitein the middle and surrounded by brownish yellow color and the edges were colorless. The opposite surfaceof the colony looks flat and slightly reflexed and orange to brown and the edges were colorless. Observationmicroscopically, the fungi showed a large macroconidia with a thick cell wall and contains 6-12 cells andoval microconidia with a small size and found in few along the hyphae. Based on the research it can beconcluded that 17 of 50 (34%) samples of dogs with dermatophytosis are Microsporum canis.
Keywords: isolation, identification, Microsporum canis, dog